Arteriovenózní pístĕl jako komplikace biopsie ledvin - Horcicka, V; Krejcí, K; Zadrazil, J; Vrublovský, P; al Jabry, S; Köcher, M; Bachleda, P (Vnitrni lekarstvi, 2002)
Renal biopsy is nowadays considered a relatively safe and routine examination method in nephrology. Its development was made possible by extension of sonography and introduction of modern automatic bioptic sets. Relatively frequent complications of biopsy include macrohaematuria, perirenal haematomas and AV fistulae. The majority of complications is unimportant from the clinical aspect. Some 30% fistulae do not recede spontaneously and gradual remodelling of the circulation near the fistula may lead to the development of complications. In the submitted paper the authors inform on the case of a 55-year-old woman where 24 hours after biopsy of a renal graft a sonographically revealed arteriovenous fistula closed spontaneously within one month; the case of a 40-year-old woman where 5 days after biopsy progression of a subcapsular haematoma and manifestation of a fistula occurred, and a 35-year-old man who developed 6 years after biopsy gradually an arteriovenous fistula with uncontrollable hypertension, hypercirculation syndrome and functional deterioration of the transplanted kidney. Superselective embolization led to improvement of the circulatory sequelae of the vascular shunt but did not have a favourable impact on renal function. Analysis of hitherto assembled experience indicates that direct ultrasound control of biopsy is effective. Because the manifestation of possible complications of biopsy need not follow immediately after the operation ultrasound follow up of native and transplanted kidneys after biopsy is justified even after a longer time interval after the operation.
Keywords: jehlová biopsie; Biopsy, Needle; Middle Aged; mužské pohlaví; Arteriovenous Fistula; arteria renalis; Adult; Renal Artery; ženské pohlaví; Renal Veins; Humans; ledviny; venae renales; lidé středního věku; arteriovenózní píštěl; dospělí; Kidney; Female; lidé; Male